Challenges in prosecuting high sea piracy under Malaysian law / Nazira Miswan, Nur'Ain Zaharudin, Nur Syamilah Mohd Amin - Miswan, Nazira; Zaharudin, Nur'Ain; Mohd Amin, Nur Syamilah (2011)
From literature review as well as the background of this concept paper, it is apparent that the question on the challenges in prosecuting high seas piracy in Malaysia can be effectively addressed by carefully examining the strength and the weakness of the Malaysian Law. This needs to be done in order to identify the gaps that need to be filled on the absence of specific legislation to prosecute high seas piracy under Malaysian law. Besides that, there are a lot of other challenges faced by Malaysian government to prosecute high seas piracy in Malaysia. Hence, these challenges can be overcome if Malaysia to enact a new law or amend existing law to include proviso on high seas piracy, in order to do that, the Parliament has to pass an Act, adapted provisions under United Nation Convention Law of the Sea (UNCLOS 1982) especially on piracy. The cooperation with adjacent states is also needed in order to maintain the safety of the territorial waters as well as the high seas.